The Urokinase-receptor (CD87) Is Expressed in Cells of the Megakaryoblastic Lineage - Wohn, Karl-Dieter; Kanse, Sandip M; Deutsch, Varda; Schmidt, Thomas; Eldor, Amiram; Preissner, Klaus T (Thrombosis and Haemostasis, 1997)
Megakaryocytopoiesis is governed in the bone marrow microenvironment by cellular interactions that include various adhesion receptor systems and pericellular proteolysis for proper regulation of cell motility and differentiation. In order to define the role of cell surface molecules required for these processes, we searched for protease receptors on these cells. In an in vitro system utilizing different cell lines of the megakaryoblastic lineage (MEG-01, Dami), low level surface expression of the urokinase (uPA) receptor was noted. Following stimulation with phorbolester (PMA), a 3-6 fold higher expression of uPA receptor over a period of up to 5 days could be observed by fluorescent activated cell-sorting as well as by direct ligand-binding of amino-terminal fragment of uPA or vitronectin. Together with elevated expression of αIIbβ3-integrin (glycoprotein IIb/IIIa complex), double immuno-fluorescence staining of stimulated cells confirmed the increased cell surface localization of uPA receptor. Semi-quantitative RT-PCR, ligand blot analysis and measurement of cell-bound proteolytic activity revealed a differentiation-dependent upregulation of the uPA receptor expression in megakaryoblastic cell lines as in monocytic cells. Due to its glycolipid anchorage, incubation with phosphatidyl-inositol-specific phospholipase C reduced uPA receptor-mediated ligand binding by about 60%. uPA receptor mRNA was expressed in cultured megakaryocytes derived from bone marrow, whereas no uPA receptor mRNA was detectable in platelets. These results indicate a differentiation-dependent increase in the expression of uPA receptor in megakaryoblastic cells. The characteristics of surface expression and functionality of the receptor on megakaryocytic cells may influence their maturation by regulating cellular communication in the bone marrow micro-environment.